Process parameters influence the mechanical properties and nugget diameter of AISI 316 stainless steel during resistance spot welding - Hamzah, Mahmood Mohammed; Barrak, Osamah Sabah; Abdullah, Isam Tareq; Hussein, Sabah Khammass (Zielona Góra: Uniwersytet Zielonogórski)
Resistance spot welding (RSW) is an important fusion welding process used in many applications, including storage tanks, pipes, and medical tools. For this, should be improved the joints and developing the process parameters and through this research will be discussed the results and concept development. Herein, 1 mm-thick AISI 316 austenitic stainless steel was welded by RSW, and the effect of the welding process parameters, such as "welding current, pulses, squeeze time, and welding time", on the mechanical properties, nugget diameter (ND), and microstructure of AISI 316 were investigated.
Keywords: nugget diameter; resistance spot welding (RSW); welding parameters; pulse; design of experiment